Clinical efficacy of direct anterior approach vs. other surgical approaches for total hip arthroplasty: A systematic review and meta-analysis based on RCTs - Zhou, Zhongsheng; Li, Yang; Peng, Yachen; Jiang, Jinlan; Zuo, Jianlin (Frontiers in Surgery, 2022)
Abstract Background: Direct anterior approach (DAA) is an accurate technique for total hip replacement through the muscle gap. Physicians who apply DAA believe that it accelerates patient recovery and results in lower rates of postoperative dislocation. However, the traditional surgical approach adherents believe that it is shorter and has fewer complications than DAA. Methods: We conducted a meta-analysis of randomized controlled trials (RCTs) to compare the outcomes of the DAA versus other surgical approaches in primary THAs. Results: We identified 15 RCTs suitable for detailed extraction of the data. The RCTs included 1450 patients with a mean age of 63 years (range 52-67). Using the DAA led to a significant improvement in the Harris Hip score (6w) by a mean difference of 4.06 points (95% confidence interval (CI) 2.54 -5.59, p < 0.01, I2=45%) at 6 weeks postoperatively. However, the 0.61 points (95% confidence interval (CI) -1.13 -2.34, p >0.01, I2=0%) at 3 months and 1.49points (95% confidence interval (CI) -1.65 -2.25, p >0.01, I2=0%) at 12 months postoperatively. In terms of dislocation rate, results show that the use of DAAs does not reduce Dislocation Rate with significant statistical heterogeneity among study groups (95% CI 0.18-2.94 P > 0.001, I2= 0%). Conclusion: The hip function of DAA was superior to posterolateral approach (PLA) and latera approach (LA) in the early days after hip replacement, especially within six weeks. However, at six months or more after surgery, the difference was not significant. The DAA did not show a lower rate of dislocation than other surgical approaches.